Impact of Scheduled Wastes on Growth: An Input-Output Approach (International Journal of Scientific Research and Management (IJSRM), 2017)
Environmental of good quality is essential for maintaining human life and protecting natural ecosystems. As the economic development contributes in enhancing standard of living, modern lifestyles on the other hand lead to potential issues in disposing the general waste. For this reason, it is essential to study on the relationship between economic growth and waste management. The main purpose of this study is to analyze impact of growth on the scheduled wastes for year 2005 by selected industries in Malaysia, then investigate how the growth brings forward the pollution sources inventory (scheduled wastes) into our environment and also to examine the impact of output estimated by final demand for year 2010 and 2015. For this purpose, the method that we have applied is input-output models to measure the interrelation between the scheduled wastes for year 2005 and growth of final demand in year 2010 and 2015. Result show that the estimates of forecasting errors have direct and indirect relationship and it has been used to make corrections for the sector-level forecasts for scheduled wastes in Malaysia for the year 2010 and 2015.